Solving the puzzle: recreational mathematics and nation-building in Singapore (1970s–2000s) - Yap, Jan Ming Shan (Nanyang Technological University, 2022)
Recreational mathematics in Singapore during the 1970s to 2000s was a means of solving the evolving puzzle of nation-building. Recreational mathematics refers to mathematics practiced for leisure, in contrast to mathematics required in the course of work or school. Due to its mathematical content and emphasis on logical thinking, recreational mathematics supposedly had the advantage of improving the minds of citizens as a rational, or educational, recreation. Rational recreation was deemed important because the development of intellectual ability was central to nation-building efforts in post-independence Singapore. Nation-building involved industrialisation, moving up from low to high value added industries, which required skilled and productive students and workers. It was also premised on the ideology of meritocracy that defined merit in terms of academic ability, which meant that intellectual development was highly valued by the state and society.